Impact of Oyo State Health Policy on the Basic Health Care Services for the People in Ibadan - Ibarapa Zone of Oyo State. - Oyerinde, Oyesegun Olufemi M. (Obafemi Awolowo University, 2014)
The study investigated the present state of basic health care services in Ibadan-Ibarapa zone of Oyo State. Also, it ascertained how the health policies of the government affect basic health care services for the people in the zone. Ten local governments in the zone were selected and 200 subjects were interviewed. The questionnaires collected were grouped into two, designated 'Type X' for illiterates and 'Type Y' for the literates. The data collected, were analysed with the use of such statistical techniques as the mean, percentages and reproducibility coefficient. The main findings of this study are as follows: 1. A general positive impact of the state policy on basic health care services for the people of Ibadan-Ibarapa zone was observed at 0.96 reproducibility coefficient for the 'type X' group and 91% positive response for the 'type Y' group.